ANALISIS UJI VALIDITAS DAN RELIABILITAS INSTRUMEN TES KEMAMPUAN BERPIKIR KRITS PADA MATERI FLUIDA STATIS - Arifatin Nadia; Desnita; Hidayati; Fuja Novitra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical thinking skills are one of the skills of the 21st century that need to be measured using valid and reliable instruments. Therefore, this study aims to analyze the feasibility of critical thinking ability test instruments on Static Fluid materials through content validity, empirical validity, and reliability tests. This study uses a quantitative approach with a descriptive method. The research subjects consisted of three lecturers of Physics Education at Padang State University as validators and 34 grade XI students of SMAN 6 Padang. The research instrument included expert validation sheets as many as 20 statement items and a critical thinking ability test in the form of six phenomena-based essay questions developed into 24 questions based on Facione's critical thinking indicators, namely interpretation, analysis, evaluation, and inference. The validity of the contents was analyzed using the Aiken's V index, the validity of the item using Pearson's Product Moment correlation, and the reliability using the Cronbach's Alpha coefficient. The results showed that the value of Aiken's V ranged from 0.7222–0.8000 so that all aspects of the instrument were declared valid. The results of the empirical validity test showed that 20 out of 24 questions were valid, while 4 were invalid. The reliability test of 20 valid questions obtained a Cronbach's Alpha value of 0.912 with a very high category. Thus, the test instruments developed meet the criteria of validity and reliability so that they are suitable for measuring students' critical thinking skills on Static Fluid materials.